PENGARUH ADVERTISING, PERSONAL SELLING, SALES PROMOTION DAN PUBLICITY TERHADAP KEPUTUSAN MEMILIH PGRI YOGYAKARTA - Restu Dwi Nugraeni; Lukia Zuraida; Indita Dwi Ariani (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to determine the effect of Advertising, Personal Selling, Sales Promotion dan Publicity of decision making in Universitas PGRI Yogyakarta. This type of research is descriptive quantitative, with the type of associative research. Population and sample in this research are college student of Universitas PGRI Yogyakarta counted 92 people. Data collection using Likert scale, with five alternative answers. Methods of data collectoin using questionnaires with multiple linier regression analysis techniques using SPSS program. The result of this research is Advertising, Personal Selling, Sales Promotion and Publicity influencing decision making of choosing Universitas PGRI Yogyakarta 38,3% and the rest equal to 61,7% influenced by the other factors. From the partial test, the most influential in decision making of choosing is advertising, while Personal Selling dan Publicity have no influence in decisoin making of choosing.